Increased perceived self-efficacy facilitates the extinction of fear in healthy participants - Zlomuzica, Armin; Preusser, Friederike; Schneider, Silvia; Margraf, Jürgen (Frontiers in Behavioral Neuroscience, 2015)
Self-efficacy has been proposed as an important element of a successful cognitive behavioral treatment. Positive changes in perceived self-efficacy have been linked to an improved adaptive emotional and behavioral responding in the context of anxiety-provoking situations. Furthermore, a positive influence of self-efficacy on cognitive functions has been confirmed. The present study examined the effect of verbal persuasion on perceived self-efficacy and fear extinction. Healthy participants were subjected to a standardized differential fear conditioning paradigm. After fear acquisition, half of the participants received a verbal persuasion aimed at increasing perceived self-efficacy. The extinction of fear was assessed immediately thereafter on both the implicit and explicit level. Our results suggest that an increased perceived self-efficacy was associated with enhanced extinction, evidenced on the psychophysiological level and accompanied by more pronounced decrements in conditioned negative valence. Changes in extinction were not due to a decrease in overall emotional reactivity to conditioned stimuli. In addition, debriefing participants about the false positive feedback did not affect the processing of already extinguished conditioned responses during a subsequent continued extinction phase. Our results suggest that positive changes in perceived self-efficacy can be beneficial for emotional learning. Findings are discussed with respect to strategies aimed at increasing extinction learning in the course of exposure-based treatments.